Phenotypic characteristics of Exotic-broiler, Kampung, Male Exotic-layer, KUB-1 and Pelung chickens - Hendry Tri Saragih; F. Viniwidihastuti; R. P. Lembayu; A. R. Kinanthi; H. Kurnianto; I. Lesmana (Indonesian Center for Animal Research and Development (ICARD), 2019)
The needs for chicken meat have been dominated by meat from exotic broilers (bred from imported parent). The potential of local broilers chicken in Indonesia is expected to be able to provide the meat for national needs for chicken meat. The objective of this research was to determine the day-old-chick (DOC) phenotypic characteristics of chickens in Indonesia that have the potential as broilers. The phenotypic characteristics are in the form of body morphometry, visceral organ weight and small intestinal histo-morphology. The chickens used were the DOC type of exotic Broiler, Kampung, exotic male Layer, KUB-1 and Pelung. A total of 125 chickens consisting of 25 chickens of each strain at posthatched age were observed for its body morphometry and its visceral organ weight, and small intestinal histo-morphology. The observed data were then analyzed by similarity analysis using MVSP 3.22 to create a dendogram with the Unweighted Pair Group with Aritmetic Average (UPGMA) method. Results showed that there were 2 different clusters from the level of similarity in their characteristics. Exotic broilers had 94.65% similarity to male exotic layer chicken and 92.26% to pelung chicken, while Kampung chickens had 90.16% similarity to KUB-1Chicken. In conclusion, it is indicated that the level of similarity of the phenotypic characteristics of pelung chickens were close to the type of exotic broiler and male exotic layer chicken. This level of similarity lead to the expectation that pelung chickens potential to be a candidate for meat-type of local chicken.